Micronized milo, urea and prairie hay for growing beef heifers - Bolsen, K.; Oltjen, J.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Twenty-four individually fed heifers were used 1n two heifer trials to evaluate four combinations of micronized or dry-rolled milo and soybean meal or urea supplements 1n prairie hay growing rations. Feeding 4 to 5 lbs. of micronized milo produced an average of 17% faster and 16% more efficient gains than feeding 4 to 5 lbs. of dry-rolled milo.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Milo; Urea; Prairie hay; Heifers